Ultrasound-Guided Hydrodilatation With Triamcinolone Acetonide for Adhesive Capsulitis: A Randomized Controlled Trial Comparing the Posterior Glenohumeral Recess and the Rotator Cuff Interval Approaches - Wang, Jia-Chi; Tsai, Po-Yi; Hsu, Po-Cheng; Huang, Jian-Ru; Wang, Kevin A.; Chou, Chen-Liang; Chang, Ke-Vin (Frontiers in Pharmacology, 2021)
For patients with adhesive capsulitis, hydrodilatation is typically performed using corticosteroids with ultrasound guidance via the posterior glenohumeral recess. Recently, a new intervention technique via the rotator cuff interval has been described. This study aimed to compare the efficacy of hydrodilatation with triamcinolone acetonide via the posterior glenohumeral recess and the rotator cuff interval in patients with adhesive capsulitis. This prospective randomized controlled trial was conducted in a tertiary care center with a follow-up period of 12 weeks. We enrolled 64 patients diagnosed with shoulder adhesive capsulitis. The subjects were randomly assigned to two groups that received hydrodilatation with corticosteroid either through the posterior glenohumeral recess or though the rotator cuff interval. The injection contained 4 mL of triamcinolone acetonide (40 mg) mixed with 4 mL of 2% lidocaine hydrochloride and 12 mL of normal saline. The shoulder pain and disability index, visual analog scale for pain, and range of motion were analyzed before and at 6 and 12 weeks after the treatment. Both groups experienced improvements in the visual analog scale scores, shoulder pain and disability index scores, and range of motion throughout the study period. A significant group-time interaction was observed in terms of the visual analog scale for pain during motion (p = 0.019), favoring hydrodilatation through the rotator cuff interval. Thus, hydrodilatation through the rotator cuff interval might be a better treatment option than that through the posterior glenohumeral recess for patients with adhesive capsulitis, considering its superior effect in alleviating pain during shoulder movement.